2019
DOI: 10.18632/oncotarget.26680
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus based virus-like-vaccines targeting endogenous retroviruses can eliminate growing colorectal cancers in mice

Abstract: Endogenous retroviruses (ERVs) that make up 8% of the human genome have been associated with the development and progression of cancer. The murine model system of the melanoma associated retrovirus (MelARV), which is expressed in different murine cancer cell lines, can be used to study mechanisms and therapeutic approaches against ERVs in cancer. We designed a vaccine strategy (Ad5-MelARV) of adenoviruses encoding the MelARV proteins Gag and Env that assemble in vivo into virus-like part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…All these events lead to the generation of a novel pool of tumor-specific antigens identified in different tumor types that can be exploited as T cell targets on tumor cells [ 62 ]. HERV-derived antigens have been used to develop cancer vaccines and chimeric antigen receptor (CAR)-expressing T cells, which have been tested only in a pre-clinical setting to date [ 71 , 72 , 73 , 74 , 75 , 76 ]. Altogether, these pre-clinical studies show the safety, immunogenicity, and preliminary efficacy data, but none of these strategies have been tested in human clinical trials so far.…”
Section: Tumor Antigensmentioning
confidence: 99%
“…All these events lead to the generation of a novel pool of tumor-specific antigens identified in different tumor types that can be exploited as T cell targets on tumor cells [ 62 ]. HERV-derived antigens have been used to develop cancer vaccines and chimeric antigen receptor (CAR)-expressing T cells, which have been tested only in a pre-clinical setting to date [ 71 , 72 , 73 , 74 , 75 , 76 ]. Altogether, these pre-clinical studies show the safety, immunogenicity, and preliminary efficacy data, but none of these strategies have been tested in human clinical trials so far.…”
Section: Tumor Antigensmentioning
confidence: 99%
“…These vaccines were highly effective at managing to target growing colorectal carcinomas and eliminating small tumours in mice. Unlike targeting with invariant chains, using neoantigens where T-cells were the only adaptive mediators of tumour resistance, it was observed that the effect of therapy was dependent on both CD4 + and CD8 + T-cells combined [ 116 , 117 ]. Following the success in murine ERV, we are currently taking this concept forward targeting human ERVs.…”
Section: Adenovirus As Therapeutic Cancer Vaccines With Ervs As Tamentioning
confidence: 99%
“…This group manifested an analogous study with HERV-K(HML2) Gag protein as the promising target to elicit a long-lived T cell response against tumor in the murine model [86]. A similar strategy has also been employed through adenovirus-mediated delivery of murine melanoma-associated retrovirus (MelARV) proteins Gag and Env to form virus-like particles displaying the cancer-associated MelARV Env to the immune system in mice, which could stimulate T cell response to inhibit murine colorectal tumor growth [87]. Likewise, another group investigated the extent of vaccination protection in rhesus macaques against ERVs as means to target HIV-and cancer-associated endogenous retrotransposable elements.…”
Section: Immunotherapeutic Strategies Targeting Herv For Cancer Treatmentioning
confidence: 99%